Innovation agents : vocational education and training skills and innovation in Australian industries and firms. Volume 1 - Toner, Phillip [Verfasser]; Marceau, Jane [Verfasser]; Hall, Richard [Verfasser]; Considine, Gillian [Verfasser] (NCVER, 2004)
"Australia's competitive success with innovation-based products and services is an influential factor to its long-term prosperity. This study examines the role of vocational education and training (VET) and occupations in innovative industries and firms. The authors find VET is vital to developing knowledge and practical skills across a broad range of occupations, and people in vocational occupations are among principal sources of ideas for technological innovation. Further, innovative firms reported a high level of satisfaction with public and private training, which the authors conclude is due to the high level of consultation between firms and TAFE. However, firms identified the need for employees to develop generic skills, such as working in teams and developing problem-solving and communication skills, as an opportunity for the VET sector to meet unmet demand." (ERIC)
Keywords: S 2.3 Berufsbildungspolitik; G 2.2 Informations- / Wissensgesellschaft; G 1.2.4.1 Produktion und Gewinnung; S 3.2 Unternehmen und Behörden; I 2.3.5 Australien, Ozeanien; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Innovationsprozess; Industriebetrieb; Unternehmen; Australien